Evaluate each expression when s=9 and t=12.
3(3t + s)
A. 9
B. 24
C. 45
D. 135
(I am not asking for the answer I need help so that's why I did not put my answer down)
8 answers
When substituting values, you take the expression and just replace it with the number you're substituting it for. So 3t becomes 3(12) because t=12, and since s=9, the expression becomes 3[3(12)+9] (using brackets because that's easier). Hope that helps. Let me know if you are still confused.
which do you solve first?
What do you mean? The values of each variable are given to you (meaning t=12 and s=9). You have to substitute them in the expression and evaluate.
Put t = 12 and s = 9 into equations.
1:
3 ( 3 t + s ) = 3 * ( 3 * 12 + 9 ) = 3 * ( 36 + 9 ) = 3 * 45 = 135
Does this help?
1:
3 ( 3 t + s ) = 3 * ( 3 * 12 + 9 ) = 3 * ( 36 + 9 ) = 3 * 45 = 135
Does this help?
I am still going to try and solve but thank youuu
btw i just submitted and got 100 on my quiz (づ。◕‿‿◕。)づ
Thanks for the compliment! I'll see you around soon and I hope you have a great day as well!
Thanks For the help